Resolusi Konflik dalam Perspektif Multidimensional: Literature Review pada Pendekatan Agama, Pendidikan, dan Komunitas - Shilatul Ailivil Aimmah; Sherly Margareta; Dewi Tria Meilani; Muhammad Rafi Shidqi; Mu’alimin Mu’alimin (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The issue of conflict resolution has become an important topic in contemporary social, educational, and political studies. The complexity of conflict, encompassing dimensions of religion, culture, education, and international politics, demands a comprehensive and integrative approach to resolution. Therefore, a literature review is essential to understand trends, strategies, and remaining research gaps in this field. This study aims to review the development of literature related to conflict resolution, focusing on two main questions: (1) what are the trends in conflict resolution research in the last five years, and (2) what models have the most potential to be developed in conflict resolution. The method used is a literature review through the Google Scholar and Publish or Perish databases with the keyword "conflict resolution." From the initial search results of 20 articles, 18 relevant articles were obtained, then selected to 5 articles that met the validity criteria (2020–2025, open access, non-duplicative). The results of the study indicate three main themes: (1) conflict resolution based on religion and culture, (2) education as a means of developing conflict resolution skills, and (3) community empowerment and structural mechanisms in managing social and political conflict.